Monitoring Grid Frequency - Mohd Ab Halim, Mohd Firdaus; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Ahmad, Suziana (Asian Research Publishing Network (ARPN), 2015)
The grid frequency of a 50 Hz system varies from 49.8 Hz to 50.2 Hz. Every 0.01 Hz of change in grid frequency correspond to approximately 6% to 8% of power supply dropped in the grid (S. Pourmousavi et al. 2009). Hence high resolution of measurement device is a must to monitor the grid frequency. Most frequency measurement devices such as oscilloscope usually caters high frequency measurement range. Even though some oscilloscope able to measure low frequency signal, its accuracy and resolution is not up to the challenge of measuring grid frequency. Phasor Measurement Unit (PMU) uses by most power system company is not economical to be used by small scale power generation company or for research purpose. In this paper, a simple zero crossing method will be employ to measure the grid frequency with a resolution of 0.003 Hz using Arduino Uno controller. The test and validation of the frequency data took place in Europe specifically at University of Applied Science Rosenheim.